(untitled) (Eurasian Journal of Research, Development and Innovation, 2021)
The article presents an attempt to identify the prospects of using such a concept of modern literary criticism as "intertextuality" in the context of contemporary poetry. The idea of intertextuality owes its appearance and development to the creativity of representatives of French post-structuralism (Y. Kristeva, R. Barth, J. Derrida). Intertextuality points to the fundamental interrelation of all texts created by mankind. The idea of intertextuality is rooted in the previous tradition of analyzing literary works. The poem “Parsley” of one of the famous script writers, story writers, activists, Former Poet Laureate and feminists Rita Dove was taken and analyzed.